2020
DOI: 10.3389/fbioe.2020.00130
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibers as Carriers of Microorganisms, Stem Cells, Proteins, and Nucleic Acids in Therapeutic and Other Applications

Abstract: Electrospinning is a technique that uses polymer solutions and strong electric fields to produce nano-sized fibers that have wide-ranging applications. We present here an overview of the use of electrospinning to incorporate biological products into nanofibers, including microorganisms, cells, proteins, and nucleic acids. Although the conditions used during electrospinning limit the already problematic viability/stability of such biological products, their effective incorporation into nanofibers has been shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 106 publications
(149 reference statements)
0
62
0
1
Order By: Relevance
“…218 In recent years, electrospinning techniques emerged as a promising process to create PCL fibrous structures for sustained and localized gene delivery. 219,220 In order to incorporate cargo to the fibers, coaxial spinning techniques can be utilized, in which an inner jet with cargo molecules and outer jet with polymer solution overcome the limitations of single stream electrospinning. 221 In one such approach, Ad was encapsulated in PCL in a core-shell fashion for subsequent porogen-mediated release.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…218 In recent years, electrospinning techniques emerged as a promising process to create PCL fibrous structures for sustained and localized gene delivery. 219,220 In order to incorporate cargo to the fibers, coaxial spinning techniques can be utilized, in which an inner jet with cargo molecules and outer jet with polymer solution overcome the limitations of single stream electrospinning. 221 In one such approach, Ad was encapsulated in PCL in a core-shell fashion for subsequent porogen-mediated release.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…In a recent study, Zech et al cultured Schwann cells onto PLGA fibers loaded with the neuroprotective drug, Nimodipine, and found that sustained release of Nimodipine from PLGA fibers significantly reduced Schwann cell death from osmotic and heat stress and, although not significant, slightly reduced Schwann cell death from oxidative stress compared to control PLGA fibers [ 159 ]. Loading proteins, such as growth factors, hormones, and enzymes, into electrospun fibers can significantly enhance their regenerative potential in the PNS as well as throughout the body [ 160 , 161 ]. Neurotrophic growth factors, such as nerve growth factor (NGF), neurotrophin-3 (NT-3), brain-derived neurotrophic factor (BDNF), and glial cell line-derived neurotrophic factor (GDNF), are commonly employed in biomaterials for neural repair due to their ability to enhance neuron survival, axonal growth, and Schwann cell migration [ 162 , 163 , 164 , 165 , 166 ].…”
Section: Peripheral Nervous System Glia and Electrospun Fibersmentioning
confidence: 99%
“…The biological products mentioned here include living cells and viruses, as well as their components such as proteins and nucleic acids 127 . Biological products are primarily intended to be used in medicine (e.g.…”
Section: Biological Products In Nanofibersmentioning
confidence: 99%